2011
DOI: 10.1016/s0027-9684(15)30359-x
|View full text |Cite
|
Sign up to set email alerts
|

Men's Perspectives on Selecting Their Prostate Cancer Treatment

Abstract: Objective In the context of scientific uncertainty, treatment choices for localized prostate cancer vary, but reasons for this variation are unclear. We explored how black and white American men made their treatment decision. Methods Guided by conceptual model, we conducted semistructured interviews of 21 American (14 black and 7 white) men with recently diagnosed localized prostate cancer. Results Physician recommendation was very important in the treatment decision, but patient self-perception/values and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 18 publications
(34 reference statements)
3
71
0
Order By: Relevance
“…Since we could not find a published validated LPC knowledge scale, we developed our own based on a through review of the literature and qualitative studies. 9,10 The knowledge scale consisted of 11 statements about the natural history of LPC and its treatment options (eg, comparative side effect profiles, facts and myths) using the options "true," "false," or "do not know" (Table 1). Each correct answer was scored with 1 point, and the total knowledge score was the sum of all correct answers.…”
Section: Instruments and Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Since we could not find a published validated LPC knowledge scale, we developed our own based on a through review of the literature and qualitative studies. 9,10 The knowledge scale consisted of 11 statements about the natural history of LPC and its treatment options (eg, comparative side effect profiles, facts and myths) using the options "true," "false," or "do not know" (Table 1). Each correct answer was scored with 1 point, and the total knowledge score was the sum of all correct answers.…”
Section: Instruments and Measuresmentioning
confidence: 99%
“…We think this result is plausible since so many controversies and uncertainties exist surrounding the myriad treatment options for LPC and a lack of consensus even among experts regarding the best decision. 9,10,13 Another possible explanation is that when men's overall knowledge of treatment side effects and survival benefit is so low, it may not reach the threshold at which a positive impact on decisionmaking difficulty can be observed. In fact, Orom et al 12 also reported that increased knowledge of LPC was associated with greater decision-making difficulty.…”
Section: 29mentioning
confidence: 99%
See 1 more Smart Citation
“…(Figure 1) These include, 1 study examining influences of partners (Zeliadt, Penson et al 2011), 2 studies examining influence of physicians (Fowler, McNaughton Collins et al 2000, Stalmeier, van Tol-Geerdink et al 2007, 16 studies comparing treatment preferences (Mazur and Hickam 1996, Hall, Boyd et al 2003, Auvinen, Hakama et al 2004, Berry, Ellis et al 2006, Zeliadt, Ramsey et al 2006, Block, Erickson et al 2007, Cox and Amling 2008, van den Bergh, van Vugt et al 2010, Davison and Goldenberg 2011, Ihrig, Keller et al 2011, Hamilton, Wu et al 2012, Penson 2012, Sidana, Hernandez et al 2012, van TolGeerdink, Willem Leer et al 2013, 4 studies on decision aids (Lin, Aaronson et al 2009, Adsul, Wray et al 2015, Violette, Agoritsas et al 2015, van Tol-Geerdink, Leer et al 2016, 7 studies (Cohen and Britten 2003, Davison, Goldenberg et al 2003, Davison, Parker et al 2004, Fischer, Visser et al 2006, Deber, Kraetschmer et al 2007, Pieterse, Henselmans et al 2011, Song, Chen et al 2013, 4 studies related to psychosocial issues of decision making (Wong, Stewart et al 2000, Kraetschmer, Sharpe et al 2004, Steginga, Turner et al 2008, Birnie and Robinson 2010, 3 studies on demographic differences in decision making (Meyer, Talbot et al 2007, Xu, Dailey et...…”
Section: Literature Searchmentioning
confidence: 99%
“…Xu et al (13) found that both physician recommendations and patient values and beliefs about prostate cancer influenced the management decision after a diagnosis of prostate cancer. However, a patient's perception of the efficacy of treatment and its side effects derived mostly from the physician influenced a patient's decision the most.…”
Section: Patient Preferences and Expectationsmentioning
confidence: 99%